Načelo primarnosti evropskega prava v luči ustavnosti ter Sodišče ES kot zakoniti sodnik - Plauštajner, Katja (Revus (Ljubljana), 2004)
The article concerns the breach of the right to a legal judge according to the German Constitution, by the national court by not taking into consideration the preliminary ruling judgment of the European Court of Justice. The German Constitutional Court also describes the content of the preliminary ruling judgment of ECJ, i.e. the principle of supremacy of European Law, and rejects the view of the national court that from the constitutional point of view, the mentioned principle is not acceptable in the case of directives.
Keywords: Evropska unija; evropsko pravo; sodišča; Sodišče Evropske skupnosti; ustavnost